2021
DOI: 10.3390/medicina57090927
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Seroprevalence to Toxoplasma gondii, Cytomegalovirus and Rubella Virus in Childbearing Women from Western Romania

Abstract: Background and Objectives: Toxoplasma gondii, cytomegalovirus (CMV) and rubella virus, besides other agents, belong to a group named the TORCH complex. Research on the epidemiology of these agents in women is of particular interest, as primary infection during pregnancy could cause severe damage to the fetus. Women who had contracted infection before pregnancy develop IgG antibodies, so the fetus is protected in case of contact with the same agent. Our scope was to identify the childbearing women simultaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 24 publications
4
30
0
Order By: Relevance
“…In our study, there was a marked increase in the number of tests carried out between 2013-2016 and 2019-2022, as reported by other researchers from Romania who studied various agents in the TORCH complex [18][19][20]. Most pregnant women were from rural In regard to HSV-2 exposure, the highest prevalence percentages were recorded in the localities of Bucovat and Calafat, with values of approximately 30%.…”
Section: Discussionsupporting
confidence: 77%
“…In our study, there was a marked increase in the number of tests carried out between 2013-2016 and 2019-2022, as reported by other researchers from Romania who studied various agents in the TORCH complex [18][19][20]. Most pregnant women were from rural In regard to HSV-2 exposure, the highest prevalence percentages were recorded in the localities of Bucovat and Calafat, with values of approximately 30%.…”
Section: Discussionsupporting
confidence: 77%
“…The main pathogens that could cross the placenta following the infection of a pregnant woman and cause severe damage to the offspring belong to the TORCH group, which represents an acronym formed by the initial letters of the names of the following pathogens ( Toxoplasma gondii , other pathogens, Rubella virus, Cytomegalovirus, Herpes simplex virus) [ 11 ]. Toxoplasma gondii (TG) is an obligate intracellular zoonotic parasite which can cause several congenital malformations if an acute primary infection occurs during pregnancy [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of 341 (88.11%) reactive samples 31 . A similar study conducted by Mocanu et al, in 2021, reported that 38 % of patients were positive for TORCH although the same diagnostic techniques for example ICT and CMIA were applied for the detection of Toxoplasma, CMV, and RV 32 . A study documented from the western area of Romania showed a very high prevalence of CMV 91.8 % among women in the reproductive period 33 .…”
Section: Discussionmentioning
confidence: 88%
“…The maximum number of pregnant women was positive 77.2 % in the age group of 26-35 years 46 . The rate of simultaneous seropositivity to, CMV, Toxoplasma gondii, and Rubella virus among Romanian pregnant women reduced significantly between 2008---2010, and 2015-2018 while the susceptibility to these infections increased 32 .…”
Section: Discussionmentioning
confidence: 91%